On narrative (re)imagining in the age of pandemic: Editor’s Introduction - Mariaelena Bartesaghi (Qualitative Research in Medicine & Healthcare, 2020)
This issue, that has been realized and published during the difficult period of the global pandemic, is the result of many efforts and for this I would like to thank the editorial team and all the wonderful contributors, readers and reviewers of Qualitative Research in Medicine & Healthcare. This issue opens with a beautiful piece on narrative as aesthetic re-imagining and closes with an article on telemedicine, taking us through both a historical and symbolic timeline of our how the stories of our lives have changed as the authors’ submissions illuminate the synchronicities of the human condition and the unexpected challenges of healthcare (and the process of academic publishing!). (...)